1941
DOI: 10.1084/jem.73.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Transplantation of Mammalian Tumors

Abstract: A series of experiments was undertaken in an attempt to transplant rabbit tumors to animals of alien species using the anterior chamber of the eye as an inoculation site. The uterine tumor H-31 and the breast tumors T-36 and B-240 were successfully transplanted to all the various animals tried, including guinea pigs, swine, goats, and sheep, and the H-31 and T-36 tumors were maintained by serial transfer in the two first species. On the other hand, all attempts to transfer the Brown-Pearce tumor to guinea pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

1950
1950
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(20 citation statements)
references
References 8 publications
0
16
0
4
Order By: Relevance
“…Green et al [60] observed that H-31 rabbit carcinoma tumor implanted into the eyes of guinea pigs did not vascularize and failed to grow for 16-26 months. The transplants remained at a size of approximately 2.5 mm in diameter for the duration of the experiment.…”
Section: Experimental Models Of Human Tumor Dormancymentioning
confidence: 99%
“…Green et al [60] observed that H-31 rabbit carcinoma tumor implanted into the eyes of guinea pigs did not vascularize and failed to grow for 16-26 months. The transplants remained at a size of approximately 2.5 mm in diameter for the duration of the experiment.…”
Section: Experimental Models Of Human Tumor Dormancymentioning
confidence: 99%
“…For solid tumors to proliferate beyond a certain size, tumor blood vessels are indispensable (1)(2)(3). Many studies on vessel formation and morphology have been reported, and will not be reviewed here.…”
Section: Introductionmentioning
confidence: 99%
“…Folkman and others first showed that, in the absence of vascularization, tumor growth arrested when the tumor reached 2–3 mm in diameter, presumably owing to limited diffusion of oxygen, nutrients, and waste products. Furthermore, small, dormant tumors would quickly resume expansion when allowed to initiate neovascularization 35…”
Section: Angiogenesis Tumor Growth and Antiangiogenesismentioning
confidence: 99%